2021
DOI: 10.3390/ijms221910656
|View full text |Cite
|
Sign up to set email alerts
|

Opposing Roles of GSK3α and GSK3β Phosphorylation in Platelet Function and Thrombosis

Abstract: One of the mechanisms by which PI3 kinase can regulate platelet function is through phosphorylation of downstream substrates, including glycogen synthase kinase-3 (GSK3)α and GSK3β. Platelet activation results in the phosphorylation of an N-terminal serine residue in GSK3α (Ser21) and GSK3β(Ser9), which competitively inhibits substrate phosphorylation. However, the role of phosphorylation of these paralogs is still largely unknown. Here, we employed GSK3α/β phosphorylation-resistant mouse models to explore the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 53 publications
(79 reference statements)
0
5
0
Order By: Relevance
“…Meanwhile, the intensity of GSK‐3β in the spinal cord of CIA group was increased ( p < 0.05 vs. control group, Figure 5F,H), while AB4 administration decreased the intensity of GSK‐3β ( p < 0.05 vs. CIA group, Figure 5F,H). The expression level of pGSK‐3β Tyr216 as an active site for GSK‐3β 37 which was upregulated in the CIA group ( P < 0.05 vs. control group, Figure 5G,I) and was reduced following AB4 treatment ( p < 0.05 vs. CIA group, Figure 5G,I).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the intensity of GSK‐3β in the spinal cord of CIA group was increased ( p < 0.05 vs. control group, Figure 5F,H), while AB4 administration decreased the intensity of GSK‐3β ( p < 0.05 vs. CIA group, Figure 5F,H). The expression level of pGSK‐3β Tyr216 as an active site for GSK‐3β 37 which was upregulated in the CIA group ( P < 0.05 vs. control group, Figure 5G,I) and was reduced following AB4 treatment ( p < 0.05 vs. CIA group, Figure 5G,I).…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the intensity of GSK-3β in the spinal cord of CIA group was increased (p < 0.05 vs. control group, Figure 5F,H), while AB4 administration decreased the intensity of GSK-3β (p < 0.05 vs. CIA group, Figure 5F,H). The expression level of pGSK-3β Tyr216 as an active site for GSK-3β 37 It is reported that GSK-3β activation increases Drp1 GTPase activity and promotes mitochondrial fission via regulating Drp1 phosphorylation. 38 Compared to control group, CIA inducement increased the intensity of spinal Drp1 (p < 0.05 vs. control group), upregulated the phosphorylation of Drp1 at Ser616 (p < 0.05 vs. control group) and downregulated phosphorylation of Drp1 at Ser637 (p < 0.05 vs. control group).…”
Section: Ab4 Decreases Spinal Gsk-3β/drp1 Signalling Activitymentioning
confidence: 99%
“…Therefore, the stimulation of platelets which is induced by the activation of GSK3β could lead us to serious problems. For example, it has been shown that the activity of this enzyme directly contributes to increased platelet aggregation in response to stimulation of PARs receptors by thrombin 22 . S ome research has suggested a variety of potential benefits associated with inhibiting the activity of this enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that GSK-3 functions as a negative regulator of platelet function, but the underlying mechanism has not been examined in detail. GSK-3 is reported to be a downstream signaling molecule of Akt that phosphorylates GSK [20]. GSK-3 is a Ser/Thr kinase, which is inhibited by the phosphorylation of an N-terminal Ser residue (GSK-3α at Ser 21 , GSK-3β at Ser 9 ).…”
Section: Discussionmentioning
confidence: 99%